CLINICAL AND IMMUNOPATHOLOGIC CHARACTERISTICS OF EARLY NEONATAL SEPSIS IN INFANTS OF DIFFERENT GESTATIONAL AGE AND CLINICAL AND ECONOMICAL EVALUATION OF IMMUNOSUPPORTIVE THERAPY EFFICACY - I.G. Soldatova; L.L. Pankratyeva; M.V. Degtyareva; V.V. Omelyanovskiy; M.V. Avksentyeva; N.D. Sveishnikova; F.M. Tsfasman; Т.V. Kulinchik; Е.V. Derkach ("Paediatrician" Publishers LLC, 2011)
Study objective - to study clinical and immunopathologic characteristics of early neonatal sepsis in infants of different gestational age and to perform clinical and economical evaluation of immunosupportive therapy with Pentaglobin efficacy in complex treatment of this disease. 79 infants diagnosed with neonatal sepsis were included into prospective study. These patients were divided into 3 subgroups in order to evaluate clinical and economical efficacy of immunosupportive therapy: subgroup A (n = 38) - patients receiving. Pentaglobin as part of basic complex treatment from 3-6 days of life; subgroup B (n = 27) - from 7-10 days of life; subgroup C  (n = 27) - patients treated without Pentaglobin. Proven high clinical and economical efficacy of immunoglobulin preparations as a part of complex treatment of neonatal sepsis allows to recommend this type of therapy for a wide application in neonatology as a part of neonatal sepsis treatment. Key words: early neonatal sepsis, prematurity, extremely low body mass, immunosupportive therapy, intravenous immunoglobines, clinical and economical analysis, neonatal sepsis. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 52-61)